Biologia reprodutiva do cíclídeo neotropical ornamental acará disco, Symphysodon discus Heckel, 1840 (Osteichthyes: Perciformes: Cichlidae) - Câmara, Mércia Rocha da (Universidade Federal de São Carlos, 2004)
The Neotropical cichlid fish red discus, Symphysodon discus Heckel, 1840 originates from the Amazonian basin. Though this species is popularly used in aquaria and is exported as an ornamental fish, it has not been intensively studied. As such, this work was carried out with an objective to study the reproductive biology of this species. Eighty individuals of both sexes of different body sizes and in different stages of gonadal development were used in this study. The gonads were examined macroscopically in order to observe the maturation stages and histological staining was used for microscopic observations. The fecundity, type of spawning and the gonadosomatic index were determined. Aggressive interactions and territoriality between mature males of different body sizes were observed in neutral situation. The results of macroscopic observations of the gonads of both sexes showed the four stages of gonadal development, such as, immature, maturing, mature and partially spent. Microscopic examinations showed five different phases of the ovarian development and four testicular developmental stages. The average fecundity per batch was 536 oocytes. The gonads of the mature females showed all the different phases of oocyte development indicating the multiple spawning habit of this species. The mature males in the reproductive phase manifested aggression, territoriality and defence of territory, exhibiting differences in body size, degree of aggression and capacity of territorial defence. The bigger males were more aggressive than the smaller males. The males with established territories were preferred by the females for courtship.
Keywords: Peixe; Acará (peixe); Reprodução; Peixe ornamental; Biologia; CIENCIAS BIOLOGICAS::ECOLOGIA